Nuclear angiography in convalescent phase of myocardial infarction. Serial study of left ventricular performance. Issue 5 (May 1980) - Rodger, J C; Railton, R; Young, K C; Lakhani, A K; Ghouri, M A
Abstract : Electrocardiograph-gated blood pool scans (anteroposterior and left anterior oblique projections) were recorded in 30 patients seven to 10 days after myocardial infarction. Left ventricular ejection fractions (mean 0.26 +/- 0.10) were lower on average than values previously obtained in 11 normal subjects (mean 0.52 +/- 0.06) and correlated broadly with the clinical assessment of left ventricular performance. Ejection fractions were lower in anterior (mean 0.21 +/- 0.09) than inferior (mean 0.32 +/- 0.08) infarcts. Abnormal wall motion was detected in 11 of 15 anterior infarcts and in six of 13 inferior infarcts: mean ejection fractions associated with global asynergy, segmental asynergy, and normal wall motion were 0.15, 0.26, and 0.36, respectively. Twenty-four patients were reinvestigated two months later. Though there was some change in the clinical status of eight patients, wall motion and ejection fraction were unchanged (mean difference -0.005 +/- 0.036). Twelve patients were reinvestigated six months after infarction. The ejection fraction for the group was significantly lower than the values obtained at 10 days and two months, and four individual changes were significant when compared with the first study. Changes in wall motion were observed in one patient. From this radionuclide study, we conclude that ejection fraction and wall motion do not improve after the early convalescent phase of myocardial infarction.